Remotely Operated Vehicle (ROV) Untuk Eksplorasi Bawah Air Di Lingkungan Industri Perkapalan - R A Septian; A Rahmania; M I Nugraha; Yudhi Yudhi (Manutech : Jurnal Teknologi Manufaktur, 2017)
Remotely Operated Vehicle (ROV) is one of the robots that are being developed in Indonesia for exploring underwater potential. In this final project, the ROV was designed and controlled by Arduino for diving underwater with maximum depth of 30 meters. The application of ROV is that to take pictures and record video of underwater environment in real time by using camera monitored through a PC. The construction and the electronics device of the ROV were made waterproof. The actuator used was bilge pump motor 1100GPH 12 Volt as thruster motor. The thruster driver used was a two channel-relay and the vision system of robot was a CCD camera. Based on the results, it was obtained that the ROV was able to move according to the commands provided by operator using a remote control. At three meters depth, the robot can move forward with average speed of 0.161m/s. For up and down movement at 3 meters depth, the robot can go up with average speed of 0.09 m/s and down with average speed of 0.17 m/s. From the data, it can be concluded that the ROV can maneuver and use the camera properly.